What Works and What Challenges in Blended Learning: A Qualitative Case Study of University Lecturers’ Perspectives at an Indonesian Public University - Hidayati, Izzanil; Rahman, Abdur; Deri, Putri Sukma; Susanti, Meria; Maputra, Yantri (Journal of Psychological Perspective, 2025)
This qualitative case study was conducted at a public university in Indonesia. Blended learning is an instructional approach that combines face-to-face meetings with online learning activities. Its effectiveness depends significantly on the appropriate integration of digital technologies, particularly during synchronous and asynchronous online sessions. This study explores university lecturers’ perspectives on the implementation of blended learning as experienced by students. Employing a qualitative research design, data were collected through open-ended questionnaires and focus group discussions (FGDs). The participants comprised 37 lecturers from Padang State University, with five of them participating in the FGDs. The findings revealed four dominant themes in lecturers’ perceptions: (1) technical challenges, (2) diminished social interaction between students and lecturers as well as among students, (3) instructional effectiveness, and (4) lecturers’ digital competence. A concise conceptual model shows that technical constraints directly reduce social interaction and instructional effectiveness, while lecturers’ digital competence can mitigate these effects through purposeful design and facilitation. The implications emphasize the need for structured institutional support, including reliable campus connectivity and learning management system uptime, a sequenced and sustained program of pedagogical upskilling for lecturers, and clear integration guidelines that align online components with course learning outcomes, so that blended learning is scalable and effective in developing country contexts with similar conditions. This study provides context rich evidence from Indonesia and contributes to the international literature on blended learning implementation.